The globalization of Chinese enterprises - Wu, Xiaobo (Henry Stewart Talks, 2014)
The Globalization of Chinese Enterprises, Booming China’s ODI, GDP growth of China, Utilization of FDI in China, China’s OFDI, China's ODI, Rationale for Chinese ODI, Motives for ODI, ODI cases: The acquisition of Steiger by Ningbo Yuren, ODI by Hikvision, The acquisition of Neucel by Fulida, Insights: from ODI to industrial upgrading, the whole ODI process, Global value chain configuration, Entry mode choice, Leverage mechanism: implications, ODI for industrial upgrading, Latecomers: how to create value through ODI?, “DMS” based global integration, Evolution process